EXAMINING RELATIONSHIP BETWEEN READING ATTITUDES AND ACADEMIC READING ACHIEVEMENT AMONG STUDENTS OF ENGLISH EDUCATION DEPARTMENT AT ALAUDDIN STATE ISLAMIC UNIVERSITY OF MAKASSAR - Dita Aristiyasari (Universitas islam Negeri Alauddin Makassar, 2019)
This study aimed to examine relation between reading attitudes and academic reading achievement. This study was conducted by using quantitative method with correlational design. Thirty students of the Fifth semester of English Education Department at Alauddin State Islamic University of Makassar were chosen randomly as the sample of this research. The data was gathered used a questionnaire to collect information related to the students’ reading attitudes. Test of English as a Foreign Language (TOEFL) especially reading section was also used to obtain information regarding students’ academic reading achievement. To verify the hypothesis, the data was analyzed by using Pearson’s Product Moment Correlation. The findings indicated that there was no relationship between reading attitudes and academic reading achievement. Students’ attitudes toward reading were positive and students’ academic reading achievement were still low, they were dominant in literal level. Nevertheless, the information related to students’ preference in some aspects of reading attitudes and their academic reading achievement may help the teacher to create a better reading teaching process in the future.